Peran Masyarakat dalam Pengelolaan Lingkungan Hidup di Kelurahan Ketang Baru Kota Manado - Virginia Yesty Putri; Grystin Djein Sumilat; Hilda Vemmy Oroh (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2023)
The focus of this research is the role of the community and government in environmental management in Ketang Baru Village, Singkil District, Manado City. Qualitative research was used. Data collection through observation, interviews and documentation. The research results show that the community plays an important role in keeping the environment clean by paying attention to cleanliness, carrying out community service and cleaning the environment, and reforestation. This is achieved by not throwing rubbish carelessly, paying attention to cleanliness, maintaining cleanliness, and carrying out supervision. The local government shows its concern through education about environmental management, financial assistance for environmental management, and assistance with rubbish bins and rubbish trucks that arrive on time.